SME Resilience in the Face of COVID Disruption: A Conceptual Framework - Ahmad Mahmoud, Mahmoud; Mahmoud, Ahmed; Aftan Abdullah, Yousif; Musa Garba , Mahabub (Journal of Economics and Administrative Sciences, 2024)
The effect of COVID-19 on firms’ operations has been the worst of any previous epidemic. The overall supply chains, corporate operations, and performance have all been impacted by the COVID-19 pandemic, making small and medium-sized organizations more susceptible. At the same time, a sizable body of research-based literature demonstrates the detrimental impact of disruptions on firms. There is a severe lack of literature on the effects of disruptions on performance among small and medium enterprises (SMEs) and the elements that could increase their resistance to disruptions in sub-Saharan African economies. The research suggested that disruption absorption plays a moderating role as an in-house resource to reroute and counteract the consequences of operational disruptions brought on by the COVID-19 pandemic on the performance of SMEs around the world and in Nigeria.  Paper type: Conceptual paper